Undersea Defense Development Strategy Facing the AUKUS Alliance in Maintaining National Defense in the Indonesian Archipelago Sea Route II - Primeka, Fadli; Widagdo, Setyo; Wanto, Alfi Haris (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
This study discusses the Navy's underwater defense development strategy, especially that of Koarmada II, to overcome challenges in maintaining national security in the ALKI II region, especially the submarine threat in connection with the formation of the AUKUS alliance. This research uses a qualitative method approach based on case studies. Quantitative methods will be used to assign weights to the internal and external factors affecting the development of the Navy's strength, using these weights, this research will identify the best strategy that can be used by Indonesia in facing these challenges. Data for this research will be collected through interviews, document analysis, and literature review. There are seven main informants, namely, the Operations Assistant of Koarmada II; Commander of Koarmada II Escort Ship Unit; Commander of Koarmada I Escort Ship Unit; Commander of Koarmada II Submarine Unit; Commander of KRI Raden Eddy Martadinata-331 Koarmada II Escort Ship Unit; Commander of Banyuwangi Navy Base; and Commander of KRI Ardadedali-404 Koarmada II Submarine Unit. SWOT analysis is used to identify and formulate several strategies for developing the strength of the Navy. SWOT analysis is used in the development strategy integrated with the threat corridor around the ALKI II region. The data validation process used is the Content Validation Index (CVI), to provide an analysis of the results in the SWOT questionnaire.